ANALISIS KUALITAS PELAYANAN KANTOR DESA KEDUNGRINGIN, KECAMATAN TUNJUNGAN, KABUPATEN BLORA DALAM MENINGKATKAN KEPUASAN MASYARAKAT - Yuliati; Murtadlo, Muhamad Nukha (Jurnal Daya Saing, 2025)
Public services at the village level still face various obstacles, particularly in terms of speed, accuracy, and technology utilization. The purpose of this study is to analyze the quality of services provided by the Kedungringin Village Office, Tunjungan Subdistrict, Blora Regency in improving community satisfaction. This study uses a qualitative descriptive method and was conducted at the Kedungringin Village Office, Tunjungan Subdistrict, Blora Regency. Data collection techniques included observation, interviews, and documentation. Informants in this study consisted of the Village Head, village officials, and village residents. The results of the study indicate that services already cover five dimensions (tangible, assurance, reliability, empathy, and responsiveness) but still face challenges in computerization and limited human resources. In conclusion, services at the Kedungringin Village Office are already quite good but need to be improved through digitalization and the addition of human resources to achieve more optimal services.   Keywords: Service Quality, Community Satisfaction, Kedungringin Village, Public Services